The Impact of Education Character on Learning Activity of Madrasah Aliyah Students in Manado - Modeong, Merriam; Ratumbuisang, Keith Francis; Hasibuan, Alfiansyah (Jurnal Ilmiah Iqra', 2024)
The Impact of Education Character on Learning Activity of Madrasah Aliyah Students In Manado. This research aims to determine the impact of Education Character on the learning activities of Madrasah Aliyah (MA) students in Manado City. This is quantitative research, and the population of this study were all class XII MA students in Manado City. At the same time, the sample in this study consisted of 78 students, formulated using an accidental sampling technique. Data analysis uses simple linear regression analysis.The research results reveal that the variable Furthermore, the t-count value is 7.524, which means it is greater than the t table value = 1.665 with N=78 (7.524>1.665). Furthermore, it can be stated that this research rejects the H0 decision, which means that Education Character has a positive and significant impact on the learning activities of Madrasah Aliyah students in Manado City